2015
DOI: 10.1038/ncomms8333
|View full text |Cite
|
Sign up to set email alerts
|

γ-secretase directly sheds the survival receptor BCMA from plasma cells

Abstract: Survival of plasma cells is regulated by B-cell maturation antigen (BCMA), a membrane-bound receptor activated by its agonist ligands BAFF and APRIL. Here we report that γ-secretase directly cleaves BCMA, without prior truncation by another protease. This direct shedding is facilitated by the short length of BCMA's extracellular domain. In vitro, γ-secretase reduces BCMA-mediated NF-κB activation. In addition, γ-secretase releases soluble BCMA (sBCMA) that acts as a decoy neutralizing APRIL. In vivo, inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
262
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 297 publications
(293 citation statements)
references
References 55 publications
11
262
4
1
Order By: Relevance
“…The presence of sBAFF‐R in human SLE sera has not previously been described. The present study confirmed the presence of both sTACI and sBCMA in sera from SLE patients, in a larger and better‐defined cohort than previously reported . Both serum sTACI and sBCMA, but not sBAFF‐R, were significantly higher in SLE than in HC.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The presence of sBAFF‐R in human SLE sera has not previously been described. The present study confirmed the presence of both sTACI and sBCMA in sera from SLE patients, in a larger and better‐defined cohort than previously reported . Both serum sTACI and sBCMA, but not sBAFF‐R, were significantly higher in SLE than in HC.…”
Section: Discussionsupporting
confidence: 90%
“…Serum concentrations of BAFF were also increased in SLE compared to HC, but this association was attenuated after adjusting for age and ethnicity. Higher serum sTACI and sBCMA concentrations were previously reported in SLE . It is noteworthy that no significant association was found between serum BAFF and any of its soluble receptors in SLE in the present study.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Peschon et al, 1998;McIlwain et al, 2012;Laurent et al, 2015), we now report that DR6 is a striking exception. While for most TNFRSF members the protease-mediated shedding is a mechanism to terminate their receptor function (e.g.…”
Section: Introductionmentioning
confidence: 49%
“…40,41 Nevertheless, TACI serves to maintain BLIMP-1 expression and thus supports the differentiation and survival of long-lived plasma cells. [43][44][45] In contrast to mice, humans express both short and long isoforms of TACI. 40,41 In addition to a direct regulatory function, loss of surface TACI or of the soluble decoy receptor may account for B cell hyperplasia because of reciprocally increased serum BAFF and APRIL levels.…”
Section: Baff Family Receptorsmentioning
confidence: 99%